Functional Network Alterations as Markers for Predicting the Treatment Outcome of Cathodal Transcranial Direct Current Stimulation in Focal Epilepsy - Hao, Jiaxin; Luo, Wenyi; Xie, Yuhai; Feng, Yu; Sun, Wei; Peng, Weifeng; Zhao, Jun; Zhang, Puming; Ding, Jing; Wang, Xin (Frontiers in Human Neuroscience, 2021)
Background and Purpose: Transcranial direct current stimulation (tDCS) is an emerging non-invasive neuromodulation technique for focal epilepsy. Because epilepsy is a disease affecting the brain network, our study was aimed to evaluate and predict the effectiveness of cathodal tDCS (ctDCS) by analyzing the ctDCS-induced functional network alterations. Methods: Either the active 5-day, -1.0 mA, 20-minute ctDCS or sham ctDCS targeting at the most active interictal epileptiform discharge regions was applied to nineteen patients suffering from focal epilepsy. The functional networks before and after ctDCS were compared employing graph theoretical analysis based on the functional magnetic resonance imaging (fMRI). A support vector machine prediction model was built to predict the effectiveness of ctDCS using the graph theoretical measures as markers. Results: Our results revealed that the mean clustering coefficient and the global efficiency decreased significantly, as well as the characteristic path length and the mean shortest path length of the stimulation sites in the fMRI functional networks increased significantly after ctDCS only for the patients with effective responses to the active ctDCS. Our prediction model achieved the mean prediction accuracy of 68.3% (mean sensitivity: 70.0%; mean specificity: 67.5%) after the nested cross validation. The mean area under the receiver operating curve was 0.75, which showed good prediction performance. Conclusion: The present study demonstrated that the effectiveness of ctDCS was related to the topological alterations in the functional networks of epilepsy patients detected by fMRI. The graph theoretical measures were promising for clinical prediction of ctDCS treatment outcome.